THE ROLE OF ENERGY CONSUMPTION IN GREEN BUSINESS AND GREEN ECONOMIES IN 5GO-GREEN COUNTRIES - Rusiadi, Rusiadi; Ulfa, Fatia; Efendi, Bakhtiar (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The issue to be addressed in this study is how economic policies and other outside variables affect the supply and consumption of energy, as well as how to develop efficient supply and consumption strategies for the economy. Simultaneous regression is used in the data analysis process. Green technology and green business have a good but not statistically significant association, according to the simultaneity research results. Green business and green investment are positively and significantly correlated. There is a strong and positive correlation between green building and green business. There is a strong and positive correlation between green business and the green economy. It is known from the simultaneity analysis results that emission and the green economy have a positive but not statistically significant link. There is a slight but favorable correlation between green finance and the green economy. There is a strong and positive correlation between energy usage and the green economy. There is a slight but positive correlation between green building and the green economy.